Antibiotic-Loaded Polymethylmethacrylate Beads and Spacers in Treatment of Orthopedic Infections and the Role of Biofilm Formation - van Vugt, Tom A. G.; Arts, Jacobus J.; Geurts, Jan A. P. (Frontiers in Microbiology, 2019)
Polymethylmethacrylate (PMMA) also referred as (acrylic) bone cement is a non-degradable biomaterial that has been used in clinical orthopaedic practice for several decades. PMMA can be used in a plain formulation, but is often used in an antibiotic-loaded formulation in (primary and revision) arthroplasty and in treatment of orthopaedic infections as prosthetic joint infections (PJI) and (chronic) osteomyelitis. In treatment of PJIs antibiotic-loaded PMMA is often used as a carrier material for local antibiotic delivery in addition to treatment with oral or parenteral antibiotics. In this case, the antibiotic-loaded PMMA is used as a spacer or as beads. Since the introduction of PMMA as an antibiotic carrier there is a tremendous amount of scientific and clinical papers that has been published, which studied numerous different aspects of antibiotic-loaded PMMA. This paper will review the research regarding basic principles of antibiotic-loaded PMMA as mechanism of action, antibiotic-release capacities, choice of antibiotics and influences on mechanical properties of PMMA. Subsequently, concerns regarding the application of antibiotic-loaded PMMA; as biofilm formation, antibiotic resistance and local or systemic toxicity will be discussed. In addition to these subjects, the role of antibiotic loaded PMMA in treatment of PJIs and biofilms, from a clinical perspective, will be discussed in the final part of this paper.